Eksplorasi Konsep Halal-Friendly dan Potensi Unik Desa Wisata Berbasis Syariah - Astri Barokah; M Risal Aziz Saputra (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Sharia tourism is a growing global market segment in line with the increasing demand of Muslim tourists for destinations that guarantee halal aspects, comfort, and safety in accordance with Sharia principles. Tourism villages have strategic potential to be developed as Sharia tourism destinations based on local potential. This study aims to explore the concept of Halal-Friendly and identify the unique potential of villages that can be optimized within the framework of Sharia and Maqashid Sharia. This study uses a qualitative approach with a literature study method. Data were obtained from scientific literature, government regulations, and official reports, then analyzed using qualitative content analysis and conceptual analysis. The results show that the implementation of Halal-Friendly in tourism villages must be carried out comprehensively through three main pillars: accommodation, consumption, and activities. The accommodation pillar covers cleanliness, privacy, and worship facilities; the consumption pillar emphasizes the guarantee of halal and thayyib in local MSME products while the activity pillar focuses on guidelines for social ethics in accordance with Sharia. Furthermore, the village's unique potential in the form of local wisdom, natural landscapes, and creative economy can become a major competitive advantage when reinforced by the principles of Hifz al-Din and Hifz al-Nafs. This integration positions the Sharia Tourism Village as a sustainable spiritual well-being destination.